TEORI TAFSIR DENGAN PENDEKATAN GENDER (Studi Kedudukan Perempuan Dalam Rumah Tangga) - Abdul Jamil Wahab; Ellys Lestari Pambayun (LP2M Universitas PTIQ Jakarta, 2021)
This study discusses the position of women in the household through interpretation theory with a gender approach. The results of this study conclude that although Islam normatively views women as noble and honorable creatures, there are interpretations of several Qur'anic verses about household leadership that are biased in partihiarchy and do not provide a portion of justice for women's rights in the household. In line with the development of science, there are interpretations that have a more equal spirit regarding gender relations. Several interpretation theories were developed using a gender perspective approach, among others, by Muhammad Abduh, Asghar Ali Engineer, Amina Wadud, and Quraish Shihab